Chemoradiation with Weekly Paclitaxel and Carboplatin in Esophageal Squamous Cell Carcinoma: A Prospective Study - Joseph, Deepa M.; Malik, Monica Irukulla; Jonnadula, Jyothi; Ahmed, Fayaz; Valiyaveettil, Deepthi (South Asian Journal of Cancer, 2021)
Objective Neoadjuvant chemoradiation (CRT) using paclitaxel and carboplatin has significantly improved the survival rates in carcinoma esophagus, especially in squamous cell carcinoma (SCC). This regimen has not been adequately explored prospectively as a definitive CRT strategy. Our aim was to evaluate the efficacy, toxicity, and compliance to this regimen in a prospective setting in locally advanced esophageal SCC.Materials and Methods Patients with locally advanced esophageal SCC were planned for definitive CRT by using weekly paclitaxel 50 mg/m2 and carboplatin area under curve 2 along with radical radiotherapy to a dose of 50.4 to 54 Gy. Treatment-related toxicity was assessed by using the common terminology criteria for Adverse Events Version 4.0, and the response was assessed by using endoscopy and computed tomography (CT) 4 to 6 weeks following CRT. The pathological response was documented for those who underwent surgery.Results Fifteen patients were included in the study, and all patients completed the planned course of radiation. The median number of chemotherapy cycles received was four. In total, 66% of the patients had delay or interruptions in chemotherapy, mostly due to neutropenia, and 66% of the patients had a clinical complete response (CR). Four patients underwent definitive esophagectomy, and the histopathology revealed pathologic CR. Overall CR rate was 80%. The median overall survival was 14 months, and 1-year survival was 57%.Conclusion Definitive CRT in esophageal SCC using weekly paclitaxel and carboplatin was relatively well tolerated with manageable toxicities and good clinical response rates. It may potentially represent a new standard of care as definitive therapy in the management of these tumors.
Keywords: esophageal squamous cell carcinoma; radical chemoradiation; weekly paclitaxel and carboplatin